2015
DOI: 10.1159/000431214
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Phenotype in Kidney Injury and Repair

Abstract: Background: Glomerular and interstitial macrophage infiltration is a feature for both the acute and chronic kidney diseases. Macrophages have been shown to play a diverse role in kidney injury and repair. Thus, macrophages may be a key cell type in acute and chronic kidney injury and repair. Summary and Key Messages: During renal inflammation, circulating monocytes are recruited and then become activated and polarized. By adapting to the local microenvironment, macrophages can differentiate into different phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 50 publications
2
89
0
Order By: Relevance
“…In general, kidney M1 macrophages are activated by pro-inflammatory cytokines such as IFN-γ, LPS and tumor necrosis factor (TNF)-α, while M2 polarization is initiated by the Th2 cytokines (IL-4, IL-10, IL-13 and so on). In addition, it is also confirmed that phagocytic uptaking of apoptotic cells may switch macrophages towards an M2 phenotype [5,30]. It has been reported that the role of macrophage in AKI is subpopulation-related.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In general, kidney M1 macrophages are activated by pro-inflammatory cytokines such as IFN-γ, LPS and tumor necrosis factor (TNF)-α, while M2 polarization is initiated by the Th2 cytokines (IL-4, IL-10, IL-13 and so on). In addition, it is also confirmed that phagocytic uptaking of apoptotic cells may switch macrophages towards an M2 phenotype [5,30]. It has been reported that the role of macrophage in AKI is subpopulation-related.…”
Section: Discussionsupporting
confidence: 52%
“…In I/R kidney, macrophages polarized into different phenotypes and exerts diverse effects [5]. We have demonstrated the Gpnmb was highly expressed in macrophages of I/R kidney.…”
Section: Typing and Identification Of Mouse Bmmφmentioning
confidence: 88%
See 3 more Smart Citations